Analysis Of Determinants Of Premature Labor Incidents In Pregnant Women - Hasnia Hasnia; Inez Vravty Lestari; Hajar Hajar; Herawaty Herawaty; Sumarni Syam (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Preterm birth is one of the main causes of neonatal morbidity and mortality. Various risk factors can influence the occurrence of preterm birth, both from medical and social aspects. This study aims to analyze the determinants of the incidence of preterm birth in pregnant women. This study used a quantitative design with a case-control approach . A sample of 120 respondents consisted of 60 cases (preterm birth) and 60 controls ( term birth ). Data were collected through medical records and questionnaires, then analyzed using logistic regression. The results showed that maternal age, nutritional status, medical history, and frequency of antenatal care (ANC) significantly influenced the incidence of preterm birth (p < 0.05). The dominant factor was irregular ANC frequency (OR = 3.5). In conclusion, improving the quality and compliance of ANC visits is very important in preventing preterm birth. Keywords: Premature Birth, Pregnant Women, Risk Factors, Antenatal Care